2017
DOI: 10.1016/j.vetimm.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of monoclonal antibodies specific for hamster leukocyte differentiation molecules

Abstract: Flow cytometry was used to identify mAbs that recognize conserved epitopes on hamster leukocyte differentiation molecules (hLDM) and also to characterize mAbs developed against hLDM. Initial screening of mAbs developed against LDMs in other species yielded mAbs specific for the major histocompatibility (MHC) II molecule, CD4 and CD18. Screening of sets of mAbs developed against hLDM yielded 22 new mAbs, including additional mAbs to MHC II molecules and mAbs that recognize LDMs expressed on all leukocytes, gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Some studies have reported that anti‐mouse CD4 clone GK1.5 is able to stain 14% to 42% of total hamster´s splenocytes. Our results showed that 20%‐30% of alive splenocytes were CD4 + which match with the literature data 9,13,14 . Regarding intracellular cytokines, we chose three key cytokines that orchestrate the immune response in VL disease.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Some studies have reported that anti‐mouse CD4 clone GK1.5 is able to stain 14% to 42% of total hamster´s splenocytes. Our results showed that 20%‐30% of alive splenocytes were CD4 + which match with the literature data 9,13,14 . Regarding intracellular cytokines, we chose three key cytokines that orchestrate the immune response in VL disease.…”
Section: Discussionsupporting
confidence: 88%
“…Based on previous studies, 7‐9 two mAbs anti‐CD4 and one mAbs anti‐CD8 were selected. Fixable viability stain 450 (FVS450, BD Biosciences) and commercially available rat anti‐mouse mAbs against TNF‐α, IFN‐γ and IL‐10 cytokines were also used (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, prime‐boost immunisation using DNA and adenoviral‐based influenza vaccines provided effective protection in experimentally challenged ferrets, with protection correlating to the capacity of CD3+ T cells to express interferon gamma (IFN‐ γ) following in vitro stimulation on peripheral blood mononuclear cells (PBMCs) with HA peptide pools . Caution should be taken when using antibodies developed for other species in ferret experiments, as there may be subsets of cells displaying variable reactivity to the antibodies . In addition, currently available anti‐ferret B‐cell antibodies such as CD79α target intracellular epitopes, requiring fixation and permeabilisation.…”
Section: Ferrets As An Immunological Model For Studying Influenzamentioning
confidence: 99%